2019
DOI: 10.1002/pon.5127
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic disparities of depressive symptoms and cytokines in hepatocellular carcinoma

Abstract: Objective To examine the associations among socioeconomic factors, depressive symptoms, and cytokines in patients diagnosed with hepatocellular carcinoma (HCC). Methods A total of 266 patients diagnosed with HCC were administered a battery of questionnaires including a sociodemographic questionnaire and the Center for Epidemiologic StudiesDepression (CES‐D) scale. Blood samples were collected to assess serum levels of cytokines using Luminex. Descriptive statistics, Mann‐Whitney U, Kruskal‐Wallis, linear regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“… Studies assessing the prevalence of depressiveness and anxiety in patients with hepatocellular carcinoma. Data for depressiveness ( n = 799 patients) are based on Mikoshiba et al (2013) , Cheng et al (2019) , Jia et al (2019) , and Wang et al (2019) , for anxiety ( n = 515 patients) on Liu et al (2017) , Jia et al (2019) , and Wang et al (2019) . …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Studies assessing the prevalence of depressiveness and anxiety in patients with hepatocellular carcinoma. Data for depressiveness ( n = 799 patients) are based on Mikoshiba et al (2013) , Cheng et al (2019) , Jia et al (2019) , and Wang et al (2019) , for anxiety ( n = 515 patients) on Liu et al (2017) , Jia et al (2019) , and Wang et al (2019) . …”
Section: Resultsmentioning
confidence: 99%
“…From the study data presented so far two things become apparent: Firstly, patients suffering from hepatobiliary cancers often experience a considerable amount of psychological distress. About a quarter of the patients suffer from depressive symptoms ( Mikoshiba et al, 2013 ; Cheng et al, 2019 ; Jia et al, 2019 ; Wang et al, 2019 ); For depression, risk factors were lower level of social status ( Cheng et al, 2019 ), less social support, low quality of sleep, more pain and higher degree of liver cirrhosis or an impairment of liver function ( Cheng et al, 2019 ). Furthermore, female sex, older age, the occurrence of metastases and hepatitis C were identified as risk factors ( Chang et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is because there are some connections between different factors, which might impact the results of prognosis. Previous studies had reported that age, race, sex, marital status, insurance, income, residence, and education level might influence the prognosis of cancer patients 10,26–30 . Based on this, our study included two more factors, COLI and poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported that age, race, sex, marital status, insurance, income, residence, and education level might influence the prognosis of cancer patients. 10 , 26 , 27 , 28 , 29 , 30 Based on this, our study included two more factors, COLI and poverty. As the smallest geographic unit in policy legislations, it is reasonable to assess individual indirectly based on the county‐level variables and previous studies adopted both individual variables and county‐level variables to construct the nomograms.…”
Section: Discussionmentioning
confidence: 99%